Host plants selection of Centranthera grandiflora Benth. and nontargeted metabolomics analysis of its parasitic and non-parasitic samples. - Song Jin; Yuchuan Li; Jun Ni; Haili Xie; Falin Lei; He Liu (PLoS ONE)
According to the previous investigation and research of our group, it was found that Centranthera grandiflora Benth. (C. grandiflora for short) might be a root hemiparasitic plant. The experiments of mixed sowing of C. grandiflora and 9 companion plants that might be hosts were conducted, and the growth, biological yield and other indexes were observed. The results showed that Cyperus iria L. was the best host for C. grandiflora, and when they were mixed sowed, C. grandiflora had a vigorous growth above ground and the haustoria connected obviously below ground, while C. grandiflora could achieve blossoming and fruiting in the same year. Next, nontargeted metabonomics analysis methods were utilized to clarify the differences in metabolites between parasitized and non-parasitized C. grandiflora. A total of 82 metabolites with significant differences were screened. The main upregulated differential metabolites of non-parasitized plants were for plant growth, while that of parasitized plants were functional compounds such as EPA. Out of 82 differential metabolites, 32 were annotated into 37 KEGG pathways. Analysis of the 37 pathways in combination with the differential metabolites showed that in addition to being involved in the synthesis pathway of iridoid terpenes, the up-regulated metabolites of parasitized plants were involved in the synthesis pathways of several functional components, while that of non-parasitic plants were involved in the subsequent catabolism of monoterpenoid compounds, as well as the metabolic pathways of nutrients synthesis and catabolism, energy generation, and phytohormone production required for plant growth.